Teaching for better learning : a guide for teachers of primary health care staff - Abbatt, Fred R. (Geneva : World Health Organization, 1992)
(NtOW^ HURAANGUJs
Includes index.
Keywords: Primary health care -- study and teaching; Allied health personnel -- education